Konfigurasi Faktor Sosial dan Psikologis dalam Partisipasi Politik: Studi Kasus Kecamatan Bangko pada Pilkada 2024 - Muhammad Rifai Setiawan; Dimasrizal Dimasrizal; Aditya Romadhon; Cholillah Suci Pratiwi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Political participation is a key indicator of local democratic quality. However, participation levels are shaped not only by structural factors but also by the configuration of social and psychological determinants underlying voting behavior. This study examines the configuration of social and psychological factors in political participation in Bangko District during the 2024 Merangin local election. A qualitative case study approach was employed. Informants were obtained using snowball sampling, including voters, community leaders, local election organizers, and campaign teams. Data were collected through in‑depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that participation is shaped by three key social factors family influence, neighborhood networks, and proximity to local political actors and three psychological factors political trust, perceived vote efficacy, and pragmatic motivation. The interaction of these dimensions produces a rational‑communal participation pattern, in which voting decisions are influenced by both benefit considerations and social pressure. These findings highlight that local political participation emerges from the interplay between social structure and individual psychological orientation. The study contributes to the literature on voting behavior in Indonesian local politics.